An Analysis of Bahasa Inggris Textbook for Grade 10 Students Published by the Indonesian Ministry of Education and Culture - Yuni Citra Wulandari; Sitti Fatimah (Journal of English Language Teaching, 2021)
The Indonesian Ministry of Education and Culture, has released a textbook entitled Bahasa Inggris Textbook for Grade 10 Students. This research aimed to determine to what extent the feasibility of the content and presentation of the textbook are. This research is an evaluative research. The data of this research were taken from Bahasa Inggris Textbook for Grade 10 Students Published by the Indonesian Ministry of Education and Culture and were analyzed using the evaluation format proposed by BSNP (2014). The evaluation format contains 18 indicators that are used to determine the quality of the textbook. The result of this research showed that the aspect of feasibility of the content is fulfilled 71.5% or categorized good, while the feasibility of the presentation got 72.3% or categorized good. By referring to the results above, this textbook can be categorized as a good reference since there are only 3 of 18 indicators that were not fulfilled; 1) the completeness of the material, 2) development of diversity, and 3) focus on the scientific approach and learning model discovery learning, and project-based learning. In contrast, the other 15 criteria have been fulfilled by this book.